Mutations in fetal genes involved in innate immunity and host defense against microbes increase risk of preterm premature rupture of membranes (PPROM). Issue 6 (23rd August 2017) - Modi, Bhavi P.; Teves, Maria E.; Pearson, Laurel N.; Parikh, Hardik I.; Haymond‐Thornburg, Hannah; Tucker, John L.; Chaemsaithong, Piya; Gomez‐Lopez, Nardhy; York, Timothy P.; Romero, Roberto; Strauss, Jerome F.
Abstract: Background: Twin studies have revealed a significant contribution of the fetal genome to risk of preterm birth. Preterm premature rupture of membranes (PPROM) is the leading identifiable cause of preterm delivery. Infection and inflammation of the fetal membranes is commonly found associated with PPROM. Methods: We carried out whole exome sequencing (WES) of genomic DNA from neonates born of African‐American mothers whose pregnancies were complicated by PPROM (76) or were normal term pregnancies ( N  = 43) to identify mutations in 35 candidate genes involved in innate immunity and host defenses against microbes. Targeted genotyping of mutations in the candidates discovered by WES was conducted on an additional 188 PPROM cases and 175 controls. Results: We identified rare heterozygous nonsense and frameshift mutations in several of the candidate genes, including CARD6, CARD8, DEFB1, FUT2, MBL2, NLP10, NLRP12, and NOD2 . We discovered that some mutations ( CARD6, DEFB1, FUT2, MBL2, NLRP10, NOD2 ) were present only in PPROM cases. Conclusions: We conclude that rare damaging mutations in innate immunity and host defense genes, the majority being heterozygous, are more frequent in neonates born of pregnancies complicated by PPROM. These findings suggest that the risk of preterm birth in African‐Americans may be conferred by mutations in multiple genes encoding proteins involved in dampening the innate immune response or protecting the host against microbial infection and microbial products. Abstract : Rare damaging mutations in fetal innate immunity and host defense genes, the majority being heterozygous, are more frequent in neonates born of pregnancies complicated by preterm premature rupture of membranes. An increased risk of preterm birth may be conferred by mutations in multiple genes encoding proteins involved in dampening the innate immune response or protecting the host against microbial infection and microbial products.